Assessing the effect of human mesenchymal stem cell-derived conditioned media on human cancer cell lines: A systematic review. (August 2021) - Raj, A. Thirumal; Kheur, Supriya; Bhonde, Ramesh; Gupta, Archana A; Patil, Shankargouda
Highlights: Anti and pro-carcinogenic MSC-CM were BM, UC, AD, WJ, DP, AM, and UT. CM from GMSC, FDMSC, and LMSC induced only anti-carcinogenic effect. CM from OMSC induced only a pro-carcinogenic effect. Abstract: Background: Mesenchymal stem cells (MSCs) exhibit differential effect (augmentation or inhibition) on cancer cells depending on the tissue of origin. Given the increasing demand to use MSCs in regenerative medicine, it is vital to ensure that the MSCs being employed are not pro-carcinogenic. Objective: To assess the effect of human MSC derived conditioned media (CM) on human cancer cell lines. Materials and methods: PubMed, SCOPUS, and Web of Science were searched using the keyword combination 'human mesenchymal stem cell and conditioned media and human cancer cell line and in-vitro'. Results: MSC-CM pro-carcinogenic molecules were IL-6, IL-8, FGF10, VEGF, PDGF, TGF-b1, IGF-1, GRO-a, OSP, MMPs, TNFα, IL-4, IL-10, IL-13, IL-17, IL-1 β, G-CSF, MCP‑1, MIP‑1α, MIP‑1β, RANTES, MIG, IP‑10, HGFa, ETX, DKK1; anti-carcinogenic molecules were IFN-β, OST, LIGHT, FRTK3, INF-γ, IP-10, LAP, IL‑1RA, IL‑2, IL-5, IL-7, IL-12, IL-15, IFN-α, IFN‑γ. Effector pathways were STAT 1, JAK2/STAT3, Ras–Raf–MEK–ERK, Wnt/β-catenin, NF-κB, ERK1/2, PI3K/ Akt/mTOR, MAPK/ERK. BMSC, ADMSC, UCMSC, WJMSC DPMSC, AMSC, and UTCMSC had a differential effect on carcinogenesis. GMSC, LMSC, FDMSC were anti-carcinogenic. OMSC was pro-carcinogenic. Conclusion: Use of MSC-CM with a pro-carcinogenic effect must be restricted in cancer patients irrespective of the nature of the application.